Case report: Strong GAD antibody positivity and type 1 diabetes-HLA-susceptible haplotype-DRB1*04:05-DQB1*04:01 in a Japanese patient with immune checkpoint inhibitor-induced type 1 diabetes - Yabuki, Shunya; Hirai, Hiroyuki; Moriya, Chihiro; Kusano, Yoshiro; Hasegawa, Takeo (Frontiers in Endocrinology, 2024)
Immune checkpoint inhibitors (ICIs) are widely used in cancer treatment; however, they can lead to immune-related adverse events, including immune checkpoint inhibitor-induced type 1 diabetes mellitus (ICI-T1DM). While fulminant T1DM is common in East Asia, ICI-T1DM has predominantly been reported in Western countries. In this report, we present the case of a 66-year-old Japanese man with type 2 diabetes mellitus undergoing dialysis for diabetic nephropathy. The patient was diagnosed with left upper lobe lung cancer, and treatment with nivolumab and ipilimumab was initiated. After 48 days, the patient experienced impaired consciousness and difficulty moving. His blood glucose levels were 815 mg/dL, and metabolic acidosis was detected, leading to a diagnosis of diabetic ketoacidosis. The patient was subsequently treated with continuous intravenous insulin. However, his C-peptide levels rapidly depleted, and new-onset ICI-T1DM was diagnosed. Although most Japanese patients with ICI-T1DM test negative for glutamic acid decarboxylase (GAD) antibodies, this case exhibited a strong positivity. Thus, we reviewed the literature on 15 similar Japanese cases, revealing a mean HbA1c level at onset of 8.7% and a mean time from ICI administration to onset of 9.7 weeks, which was shorter than that in GAD-negative cases. Moreover, human leukocyte antigen typing revealed five cases of DRB1*04:05-DQB1*04:01, including the present case, and one case of DRB1*09:01-DQB1*03:03, both of which were susceptible to T1DM haplotypes. These findings suggest that GAD antibody positivity may be associated with acute onset and disease progression in some cases of Japanese patients with ICI-T1DM. Given that the prediction of new-onset ICI-T1DM is challenging, monitoring GAD antibody levels might be useful. However, further studies with large sample sizes and validation across different racial and ethnic populations are warranted.